DAMPAK PENGGUNAAN MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN PATEM TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR - Weli Kusmira Gulo; Hesti Yunitiara Rizqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to examine the differences and the effect of the use of the Game-Based Learning model assisted by shooting board media on elementary school students’ conceptual understanding. This study was motivated by the low level of conceptual understanding among second-grade students at SD Negeri Karangjati 04, which was caused by the use of conventional learning models and less varied instructional media. This research employed a quantitative approach using a quasi-experimental design. The research subjects consisted of students in class IIA as the experimental group and class IIB as the control group, with a total of 40 students. Data collection techniques included conceptual understanding tests, observation sheets, and student response questionnaires. Data analysis was conducted through prerequisite tests, including normality and homogeneity tests, followed by an independent sample t-test and simple linear regression analysis. The results showed that there was a significant difference in students’ conceptual understanding between those who were taught using the Game-Based Learning model assisted by shooting board media and those who received conventional instruction. Furthermore, the regression analysis indicated that the Game-Based Learning model assisted by shooting board media had a significant effect on students’ conceptual understanding. Therefore, the Game-Based Learning model assisted by shooting board media is effective in improving elementary school students’ conceptual understanding, particularly at the lower grade level.